О нелинейных эллиптических системах высокого порядка, положительных по первым производным - Калита, Е.А. (Український математичний журнал, 1993)
Divergent type elliptic systems with the natural energy space Wmp⋂Wlq are considered. It is proved that, under certain restrictions imposed on the modulus of ellipticity of the lower part of the system, the generalized solutions of the system are continuous according to Holder and the Liouville theorem holds.